The COMPARISON OF LAWS ON CHILD LABOR INVOLVEMENT IN INDONESIA AND FRANCE AS SUBJECTS IN COMMERCIALIZED DIGITAL CONTENT - Aldiansyah, Devid; Ronaboyd, Irfa (Indonesian Journal of Labour Law and Industrial Relations, 2025)
The development of the digital economy has created both opportunities and challenges in protecting children's rights, particularly when children become the main subjects of monetized digital content. This phenomenon has grown rapidly in countries such as Indonesia and France, although their normative responses differ significantly. This study aims to analyze and compare the legal frameworks in Indonesia and France regarding the involvement of child labor in monetized digital content. Using a normative and comparative legal approach, and drawing on functionalism, legal transplant, and legal convergence theories, this research finds that Indonesia still faces normative ambiguity in this area, while France has developed a more specific regulatory framework through Loi n° 2020-1266 and Loi n° 2023-566. The study recommends the formulation of specific regulation in Indonesia that addresses the challenges of the digital economy in relation to child protection, by referring to international best practices. These findings are expected to contribute to national legal reform in the context of labor law and child rights in the digital space.